1991
DOI: 10.1063/1.461410
|View full text |Cite
|
Sign up to set email alerts
|

Molecular beam studies of the photolysis of allene and the secondary photodissociation of the C3Hx fragments

Abstract: Angle resolved time of flight (TOF) measurements of the fragments produced when allene is photolyzed at 193 nm are described. The two primary processes that have been identified from these measurements are the H+C3H3 and the H2+C3H2 channels. The quantum yields for these first steps are 0.89 and 0.11, respectively. Subsequent photolysis of the C3H3 radical produces H2+C3H, C3H2+H, and C2H2+CH, while the C3H2 produces C3+H2, C2H+CH, and C2H2+C. The translational energy distributions for each one of these steps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
3

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 21 publications
9
63
3
Order By: Relevance
“…The latter was observed for the first time, which is not surprising, because it is a minor channel responsible for only 1 % of the total products as extrapolated to zero laser power. The contribution of the molecular hydrogen elimination was evaluated as 7 %, slightly lower than the 11 % obtained by Jackson et al [97] This channel was found to include a multiphoton component of less than 10 % of the total C 3 H 2 + H 2 yield due to absorption of more than a single photon. Only the C 3 H 3 (H-loss) and C 3 H 2 (H 2 -loss) fragments were detected in the photodissociation of propyne, with most of C 3 H 2 resulting from a two-photon process.…”
Section: Molecular Beam Studies-photoionizationmentioning
confidence: 74%
“…The latter was observed for the first time, which is not surprising, because it is a minor channel responsible for only 1 % of the total products as extrapolated to zero laser power. The contribution of the molecular hydrogen elimination was evaluated as 7 %, slightly lower than the 11 % obtained by Jackson et al [97] This channel was found to include a multiphoton component of less than 10 % of the total C 3 H 2 + H 2 yield due to absorption of more than a single photon. Only the C 3 H 3 (H-loss) and C 3 H 2 (H 2 -loss) fragments were detected in the photodissociation of propyne, with most of C 3 H 2 resulting from a two-photon process.…”
Section: Molecular Beam Studies-photoionizationmentioning
confidence: 74%
“…It can also produce C 3 H 3 +H. The branching ratio was already determined by Jackson et al (1991) experimentally to be 0.19 for the first and 0.81 for the latter reaction. The atomic hydrogen production channel dominates over the molecular hydrogen channel.…”
Section: H 2 Chemistrymentioning
confidence: 81%
“…There are several pathways of C 3 H 2 dissociation discussed in the literature [2,12]. The major channel is expected to be an elimination of H 2 because it has the lowest activation barrier calculated to be 3.71 eV [2].…”
Section: Resultsmentioning
confidence: 99%